Discovery of 1-(1H-indazol-4-yl)-3-((1-phenyl-1H-pyrazol-5-yl)methyl) ureas as potent and thermoneutral TRPV1 antagonists. Issue 23 (1st December 2020) - Kang, Jin Mi; Kwon, Sun Ok; Ann, Jihyae; Blumberg, Peter M.; Ha, Heejin; Yoo, Young Dong; Frank-Foltyn, Robert; Lesch, Bernhard; Bahrenberg, Gregor; Stockhausen, Hannelore; Christoph, Thomas; Lee, Jeewoo
Graphical abstract: Abstract: A series of 1-indazol-3-(1-phenylpyrazol-5-yl)methyl ureas were investigated as h TRPV1 antagonists. The structure–activity relationship study was conducted systematically for both the indazole A-region and the 3-trifluoromethyl/ t -butyl pyrazole C-region to optimize the antagonism toward the activation by capsaicin. Among them, the antagonists 26, 50 and 51 displayed highly potent antagonism with Ki (CAP) = 0.4–0.5 nM. Further, in vivo studies in mice indicated that these derivatives both antagonized capsaicin induced hypothermia, consistent with their in vitro activity, and themselves did not induce hyperthermia. In the formalin model, 51 showed anti-nociceptive activity in a dose-dependent manner.